ALDH1A1 Gene Expression and Cellular Copper Levels between Low and Highly Metastatic Osteosarcoma Provide a Case for Novel Repurposing with Disulfiram and Copper. (28th January 2022) - Mandell, Jonathan B.; Douglas, Nerone; Ukani, Vrutika; Beumer, Jan H.; Guo, Jianxia; Payne, John; Newman, Rebecca; Mancinelli, Luigi; Intini, Giuseppe; Anderson, Carolyn J.; Watters, Rebecca; Weiss, Kurt
Abstract : Aldehyde dehydrogenase 1A1 (ALDH) is a cancer stem cell marker highly expressed in metastatic cells. Disulfiram (Dis) is an FDA-approved antialcoholism drug that inhibits ALDH and has been studied as a candidate for drug repurposing in multiple neoplasia. Dis cytotoxicity in cancer cells has been shown to be copper-dependent, in part due to Dis's ability to function as a bivalent metal ion chelator of copper (Cu). The objectives of this research were to test ALDH expression levels and Cu concentrations in sarcoma patient tumors and human osteosarcoma (OS) cell lines with differing metastatic phenotypes. We also sought to evaluate Dis + Cu combination therapy in human OS cells. Intracellular Cu was inversely proportional to the metastatic phenotype in human OS cell lines (SaOS2 > LM2 > LM7). Nonmetastatic human sarcoma tumors demonstrated increased Cu concentrations compared with metastatic tumors. qPCR demonstrated that ALDH expression was significantly increased in highly metastatic LM2 and LM7 human OS cell lines compared with low metastatic SaOS2. Tumor cells from sarcoma patients with metastatic disease displayed significantly increased ALDH expression compared with tumor cells from patients without metastatic disease. Serum Cu concentration in canine OS versus normal canine patients demonstrated similar trends. Dis demonstrated selective cytotoxicity compared with human multipotential stromal cells (MSCs): Dis-treated OS cells demonstrated increased apoptosis, whereas MSCs did not. CuCl2 combined with Dis and low-dose doxorubicin resulted in a superior cytotoxic effect in both SaOS2 and LM7 cell lines. In summary, ALDH gene expression and Cu levels are altered between low and highly metastatic human OS cells, canine samples, and patient tumors. Our findings support the feasibility of a repurposed drug strategy for Dis and Cu in combination with low-dose anthracycline to specifically target metastatic OS cells.